Analysis of Science Process Skills of Junior High School Students - Apriani Herni Rophi; Ruth Megawati; Yaneta Tabita Aiboy; Mivtha Citraningrum; Edoward Krisson Raunsay (Jurnal Penelitian Pendidikan IPA, 2024)
Natural Sciences (IPA) emphasizes students' science process skills in every learning process. However, looking at the facts in the field when studying science, students still tend to memorize concepts, theories, and principles without understanding the discovery process. This has an impact on the ongoing learning process being uninteresting so that students become bored and ultimately causes students' understanding of science concepts to become low. This research aims to determine the quality of science process skills of class VII students at Kanda Middle School. The research method used is quantitative. The population is all class VII students at Kanda Middle School, totaling 46 people, while the sample in this study was 23 students taken by random sampling. The instruments used are performance that assesses practicum activities as well as interview guidelines used to gather information from science teachers. Data were analyzed using the percentage value formula. This research concludes that the science process skills of class VII Kanda State Middle School students have a percentage of 70.01% in the skilled category.